A diary study of information encountering triggered by visual stimuli on micro-blogging services. Issue 1 (January 2019) - Jiang, Tingting; Guo, Qian; Xu, Yaping; Fu, Shiting
Highlights: How visual stimuli triggered IE on micro-blogging services was studied. Micro-blogging services were IE-friendly environments and rich in visual stimuli. Excluding text from visual stimuli increased users' interactions with micro-posts. Higher comprehensibility or humorousness of visual stimuli increased users' interactions with micro-posts. Applying CIT in diaries was effective for data collection in IE research. Abstract: Despite various models established to present the process of information encountering (IE), little research has been done on the stimulus that plays an essential role in attracting users' attention and eliciting the subsequent behavioral responses during an IE process. This study was particularly interested in visual stimuli which are superior to textual ones in enhancing information processing and sensory experience. A diary study of IE was conducted in the context of micro-blogging services. They demonstrate the environmental characteristics conducive to IE and are especially abundant in visual stimuli. A total of 189 valid IE incidents triggered by visual stimuli on a representative micro-blogging service were collected with an online questionnaire created based on the critical incident technique (CIT) and analyzed both quantitatively and qualitatively. As found in this study, most of the visual stimuli triggering IE excluded text or motion, and their comprehensibility and novelty were both perceived to be high while humorousness much lower. The encountered micro-posts covered a wide range of topics and were published by different types of micro-bloggers. When interacting with the posts, the participants sometimes just examined their visual or textual content, but sometimes further captured the posts by liking, reposting, commenting, and following, etc. The significant results indicate that the visual stimuli excluding text and those with higher comprehensibility or humorousness were more likely to induce intense approach to the micro-posts. These findings inform micro-bloggers of the means of engaging the audience in intense interactions with their posts to gain persistent profit or reputation. The combination of diaries and the CIT is effective for data collection in IE research.